2020
DOI: 10.1002/sys.21566
|View full text |Cite|
|
Sign up to set email alerts
|

Value and benefits of model‐based systems engineering (MBSE): Evidence from the literature

Abstract: Traditional document‐based practices in systems engineering are being transitioned to model‐based ones. Adoption of model‐based systems engineering (MBSE) continues to grow in industry and government, and MBSE continues to be a major research theme in the systems engineering community. In fact, MBSE remains a central element in the International Council on Systems Engineering (INCOSE)’s vision for 2025. Examining systems engineering literature, this paper presents an assessment of the extent to which benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
64
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(85 citation statements)
references
References 20 publications
3
64
0
1
Order By: Relevance
“…MBSE Benefits. The benefits expected of MBSE have been recently evaluated in a systematic literature review of over 800 papers related to MBSE (Henderson & Salado, 2021). This review found 48 different benefits that are claimed throughout the literature, although most of these benefit claims are stated without any supporting evidence.…”
Section: Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…MBSE Benefits. The benefits expected of MBSE have been recently evaluated in a systematic literature review of over 800 papers related to MBSE (Henderson & Salado, 2021). This review found 48 different benefits that are claimed throughout the literature, although most of these benefit claims are stated without any supporting evidence.…”
Section: Benefitsmentioning
confidence: 99%
“…The simplicity of adopting CAD makes it more straightforward to justify benefits; one can simply compare the cost of the CAD license with gains in productivity. MBSE, as a process, is more complicated and is therefore more difficult to measure benefits or calculate the ROI (Henderson & Salado, 2021). Furthermore, due to the more complex nature of the SE process compared to CAD, the period of time which MBSE is used is typically much longer.…”
Section: Benefit Comparisonmentioning
confidence: 99%
“…Recent thrust in the systems engineering (SE) community has been toward the use of models to perform SE activities [1]. This change comes from a desired conversion away from document-based SE (DBSE) to model-based SE (MBSE) to leverage potential improvements such as traceability through authoritative sources of truth [2]. However, a recent survey presented several obstacles to the adoption of MBSE in practice [3], alluding, among others, to conceptual misalignment.…”
Section: Introductionmentioning
confidence: 99%
“…The MSR CCRS COM Pre-Phase A architectural development activity was used as a case study to assess the benefits of MBSE over traditional systems engineering in achieving automatic information transfer. This research is motivated by the observation that despite the claims made in the literature that MBSE is beneficial to the development of engineered systems, there is lack of empirical evidence in the literature that supports this hypothesis [18]. Additionally, there is a limited number of case studies with side-by-side comparison of MBSE and non-MBSE approaches that provide quantitative evidence of the advantages MBSE approaches over traditional, document-based approaches [16].…”
Section: Introductionmentioning
confidence: 99%